Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Apparel and Textile yang Terdaftar di Bursa Efek Indonesia - Mumpuni, Wahyu; Indarti, Iin (Jurnal Ilmiah Aset, 2013)
The main purpose of this study was to determine whether variables that influence capital structure company were able to explain the company’s capital structure principle in the apparel and textile sector. The variables in the study were firm size, business risk, growth rate, asset structure and profitability. The population was 20 companies and the samples were 10 companies of the apparel and textile sector listed in Indonesia Stock Exchange, with the period of observation from 2009 to 2011. The technique sampling used was non probability with purposive sampling method. The model regression used was by multiple linier regression. The results showed that firm size, business risk and growth rate didn’t significantly influence capital structure. Meanwhile, two other variables, structure of assets and profitability had a negative significant influence on capital structure.